Xenon elimination kinetics following brief exposure. Issue 5 (24th June 2016) - Schaefer, Maximilian S.; Piper, Thomas; Geyer, Hans; Schneemann, Julia; Neukirchen, Martin; Thevis, Mario; Kienbaum, Peter
Abstract : Xenon is a modern inhalative anaesthetic with a very low solubility in tissues providing rapid elimination and weaning from anaesthesia. Besides its anaesthetic properties, Xenon promotes the endogenous erythropoietin biosynthesis and thus has been enlisted as prohibited substance by the World Anti‐Doping Agency (WADA). For effective doping controls, knowledge about the elimination kinetics of Xenon and the duration of traceability are of particular importance. Seventy‐seven full blood samples were obtained from 7 normal weight patients undergoing routine Xenon‐based general anaesthesia with a targeted inspiratory concentration of 60% Xenon in oxygen. Samples were taken before and during Xenon inhalation as well as one, two, 4, 8, 16, 24, 32, 40, and 48 h after exposure. Xenon concentrations were assessed in full blood by gas chromatography and triple quadrupole tandem mass spectrometry with a detection limit of 0.25 µmol/L. The elimination of Xenon was characterized by linear regression of log‐transformed Xenon blood concentrations, as well as non‐linear regression. Xenon exposure yielded maximum concentrations in arterial blood of 1.3 [1.1; 1.6] mmol/L. Xenon was traceable for 24 to 48 h. The elimination profile was characterized by a biphasic pattern with a rapid alpha phase, followed by a slower beta phase showing a first order kinetics (c[Xe] = 69.1e ‐0.26x, R 2  = 0.83, t1/2  = 2.7 h). Time in hours after exposure could be estimated by 50*ln(1.39/c[Xe] 0.077 ). Xenon's elimination kinetics is biphasic with a delayed beta phase following a first order kinetics. Xenon can reliably be detected for at least 24 h after brief exposure. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The anaesthetic Xenon has reportedly been inhaled by athletes for performance enhancement and was declared a prohibited substance by WADA in 2014. We determined the elimination kinetics of Xenon and the duration of traceability in human blood after brief exposure in patients undergoing routine Xenon‐based anaesthesia. Xenon shows a biphasic elimination pattern with a rapid alpha phase, followed by a slower beta phase of a first order kinetics and was reliably detected for at least 24 h in all patients.